2008
DOI: 10.1016/j.ejphar.2008.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve injury alters spinal nicotinic acetylcholine receptor pharmacology

Abstract: Nicotinic acetylcholine receptors are widely expressed in the rat spinal cord and modulate innocuous and nociceptive transmission. The present studies were designed to investigate the plasticity of spinal nicotinic acetylcholine receptors modulating mechanosensitive information following spinal nerve ligation. A tonic inhibitory cholinergic tone mediated by dihydro-β-erythroidine-(DHβE) and methyllycaconitine-(MLA) sensitive nicotinic acetylcholine receptors was identified in the normal rat spinal cord and cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…Consistent with our study, previous studies showed that intrathecal nicotinic receptor agonists increased withdrawal thresholds measured by paw pressure test in SNL animals. 14,27 In contrast, a previous study demonstrated that antiallodynic effect from orally administered donepezil is not affected by mecamylamine in SNL rats. 7 In normal animals, nicotinic receptors have no or little role on thermal antinociception from cholinesterase inhibition.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Consistent with our study, previous studies showed that intrathecal nicotinic receptor agonists increased withdrawal thresholds measured by paw pressure test in SNL animals. 14,27 In contrast, a previous study demonstrated that antiallodynic effect from orally administered donepezil is not affected by mecamylamine in SNL rats. 7 In normal animals, nicotinic receptors have no or little role on thermal antinociception from cholinesterase inhibition.…”
Section: Discussionmentioning
confidence: 77%
“…13,16,35 Stimulation of spinal nicotinic receptors has been reported to produce presynaptic GABA release and γ-aminobutyric acid type A receptor-mediated analgesia. 14,15,27,36 However, no previous study measured GABA concentrations in the spinal cord after stimulation of cholinergic receptors.…”
Section: Spinal Ach and Gaba Mechanisms For Donepezil Analgesiamentioning
confidence: 99%
“…2,46,67 We aimed to determine whether systemic administration of a novel selective α7 nAChR agonist, TC-7020, was also able to reverse CCI-induced neuropathic allodynia in both the ipsilateral and contralateral hind paws. CCI resulted in significant allodynic response compared with sham-treated rats, which was stable 10 days after surgery and throughout the remainder of the study in the vehicle group.…”
Section: Resultsmentioning
confidence: 99%
“…2,46,67 Choline, a naturally occurring nutritional supplement and a constituent of acetylcholine, is a selective α7 nAChR agonist. 50 Systemic administration of choline reduced hyperalgesia in the late phase of formalin 63 and was found to be effective in a rat model of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, peripheral nerve injury greatly upregulated transcripts for the α 5 and β 2 nicotinic acetylcholine receptor subunits within the spinal cord dorsal horn [37]. In another study, spinal nerve ligation resulted in an increase of the expression of several nAChR subunits ipsilaterally, including α 5 subunit [38]. Taken together, these results suggest that α 5 *-nAChRs play an important role in changes in spinal connectivity (i.e., central sensitization) induced by nerve injury in rodents.…”
Section: Discussionmentioning
confidence: 99%